A COMPARATIVE ANALYSIS OF MINAHASA FOLKLORES “TOAR LUMIMUUT” AND “SIGARLAKI LIMBAT” THROUGH WORLD LITERATURE PERSPECTIVES - Kobis, Dewi Christa; Sebayang, F. Ari Anggraini; Basri, Muh Hasan (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2024)
This study focused on analyzing Minahasa famous folklores called Toar Lumimuut and Sigarlaki Limbat. Despite just being folklores in the past, due to their popularity, they have been preserved officially in writings and have been considered as local treasure of Minahasa. In order to give them better spot in revitalization due to globalization that give more pressure to the local culture, it is necessary to take specific action to preserve and revitalize them. This study was conducted by gaining data through library research and interview, then analyzed by literary criticism called world literature by David Damrosch. There were five Minahasa local people who participated in the interview. Both of them are males while the other three are females. It is found that both folklores suit the three characteristics to be called world literature. They both are available in several translations, they are refracted in other literary worlds around the world, and they are popular and their scripts have been digitalized by official governments. The acts of comparing these two literary works through world literature perspectives are considered necessary in conveying to the Minahasa young generation and even globally that the local folklores can be classified as world literature as well and becomes the local and national treasure that should be appreciated, respected, and reserved.